Technologies and Technical Means for Smooth Plowing (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The farming system includes a whole range of different activities, among which one of the main places is occupied by the tillage system. The existing technologies and technical means for smooth plowing are analyzed. In the results of the analysis of technology and technical means of basic tillage, it was found that the combined frontal plow is of the greatest interest, simultaneously performing smooth, rowless plowing, sub-tillage loosening of the compacted layers of the middle of the cotton row spacing and the formation of ridges on the structural layers of the soil. On the basis of frontal plows, it is possible to develop combined wide-reach tools for energy-saturated tractors that perform several technological operations, taking into account the characteristics of the cotton field. The introduction of a new technology of smooth plowing and frontal plows for its implementation in the cotton growing area is at this stage a timely, important and relevant task of great scientific and practical interest.